Faktor Penyakit Infeksi, Penggunaan Obat dan Gizi Ibu Hamil terhadap Terjadinya Kelainan Kongenital pada Bayi Baru Lahir - Anita, Anita (Politeknik Kesehatan Tanjungkarang, 2017)
The incidence of congenital abnormalities ranges was from 15 per 1000 births. This study was to know the infectious factor, medicine and nutrition of mother to congenital abnormalities in newborn in Perinatology room, Bandar Lampung Hospital, in 2016. This study was quantitative research, case control study, secondary data. The population were all infants treated in the Perinatology Room of Bandar Lampung Hospital, in 2016. Sample were 112 infants (56 as cases and 56 as controls), research variables were included infectious factors, drugs, nutrition and congenital anomalies. The result showed infection factor 27 (48%), drug factor 24 (43%), and nutrient factor less 25 (45%). There were correlation of infectious factor (p-value=0,001), drug use factor (p-value=0,001), nutritional factor (p-value=0,000) with congenital abnormalities in newborn. The most dominant factor was nutritional factor (p-value=0.000) with OR = 10,132.